2006
DOI: 10.2527/jas.2006-163
|View full text |Cite
|
Sign up to set email alerts
|

Changes in caspase activity during the postmortem conditioning period and its relationship to shear force in porcine longissimus muscle1

Abstract: The objective of this study was to investigate the protease family caspases in skeletal muscle and their potential contribution to postmortem proteolysis and meat tenderization. Ten Large White gilts were slaughtered, and samples of LM were taken at 0, 2, 4, 8, 16, 32, and 192 h after slaughter and immediately snap frozen in liquid nitrogen. Samples were subsequently analyzed for caspase 3/7 and caspase 9 activity, protein levels of known caspase substrates, alpha II spectrin and poly (ADP-ribose) polymerase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 19 publications
4
66
0
Order By: Relevance
“…Caspases Caspase-9. There was a significant decrease in caspase-9 activity from 4 h to day 2 in both control and treated samples (P , 0.001; Figure 3), similar to those reported in postmortem porcine LM muscle by Kemp et al (2006). The caspase-9 activity varied significantly among the treated and control samples at 4 h and day 4 (P , 0.01).…”
Section: Mfi Valuessupporting
confidence: 81%
See 2 more Smart Citations
“…Caspases Caspase-9. There was a significant decrease in caspase-9 activity from 4 h to day 2 in both control and treated samples (P , 0.001; Figure 3), similar to those reported in postmortem porcine LM muscle by Kemp et al (2006). The caspase-9 activity varied significantly among the treated and control samples at 4 h and day 4 (P , 0.01).…”
Section: Mfi Valuessupporting
confidence: 81%
“…The caspase-3 activity significantly increased from 4 h to day 1, whereas subsequently decreased from days 1 to 2 in control (P , 0.001; Figure 5). Similarly, Kemp et al (2006) reported that there was a general decrease in caspase-3/7 activity over storage with the highest activity at 2 h in pork. In addition, Underwood et al (2008) indicated that caspase-3 activity decreased at days 3 and 10 post mortem when compared with 0 day in beef.…”
Section: Mfi Valuesmentioning
confidence: 81%
See 1 more Smart Citation
“…Ouali et al (2006) suggested that the cysteine protease family of caspases is in a better position than other proteolytic enzymes to cleave cytoskeleton, as this is their primary function in vivo. Kemp et al (2006a) indicated that caspasemediated cleavage takes place in the porcine muscles during conditioning. Kemp et al (2006b) detected caspase-3 (20 kDa) and caspase-8 (18 kDa) active fragments in the porcine muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Kemp et al (2006) investigated the relevant expression of various caspase types in different porcine skeletal muscles and reported the direct involvement of the caspase family in meat tenderisation. Moreover, Huang et al (2009) made use of DEVD-CHO (N-acetylAsp-Glu-Val-Asp-CHO), a selective inhibitor of caspase-3, and showed that it dramatically reduced the degradation of the skeletal proteins, such as nebulin, titin, troponin-T, and desmin, while the activity of calpain was not affected.…”
mentioning
confidence: 99%